Recommendation for Improvement in COVID-19 Vaccine Program in Malaysia: An Online Nationwide Qualitative Survey - Solehan, Hana Maizuliana; Mohd Rani, Mohd Dzulkhairi; Mohamed, Nurul Azmawati; Mohamed, Nurul Azmawati; Ithnin, Muslimah; Ariffien, Abdul Rasyid; Che Isahak, Che Ilina (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Maintaining high levels of vaccinations is important for public health success in any vaccination planning. Success requires a better understanding of the public’s perceptions of diseases and consequent decisions about vaccinations. This study aims to gather exploratory qualitative data on public opinion on the Malaysian Government’s COVID-19 immunization campaigns. Methods: Open-ended question on Google Form was advertised online between 2 to 17 December 2020. The questionnaire form was deactivated when saturation has been reached. The free text questions were analysed by qualitative thematic analysis by all authors on a Microsoft Excel spreadsheet. Results: Six hundred and sixty-one participants replied to the online questionnaire. Four themes emerged from the thematic analysis on suggestions for future National COVID-19 Immunisation Program. First, COVID-19 vaccine administration policy; secondly, knowledge dissemination and plan to address obstacles of public acceptances towards the vaccine proactively; thirdly, better implementation programs by the government and fourthly, using local research expertise for vaccine development and alternative medicines. Participants believe all this are essential in increasing their trust and uptake for the government’s future national COVID-19 Immunisation Program. Conclusion: This study highlights the suggestions made by the public for the Malaysian Government. These findings will help develop education and intervention strategies for new vaccine introduction to combat the COVID-19 pandemic in Malaysia. References: Hinman A, Orenstein W, Schuchat A. Vaccine-preventable Diseases, Immunizations, and the Epidemic Intelligence Service. American Journal of Epidemiology. 2011;174:S16-S22. Van Wijhe M, Tulen A, Korthals Altes H, Mcdonald S, De Melker H, Postma M, Wallinga J. Quantifying the impact of mass vaccination programmes on notified cases in the Netherlands. Epidemiology and Infection. 2018;146:716-22. Macdonald N, Comeau J, Dubé E, Bucci L, Graham J. A public health timeline to prepare for COVID-19 vaccines in Canada. Canadian Journal of Public Health. 2020;111:945-52. Bb L. COVID-19 immunization threshold (s): an analysis. medRxiv. 2021;. Rubin R. Difficult to Determine Herd Immunity Threshold for COVID-19. JAMA. 2020;324:732. García L, Cerda A. Contingent assessment of the COVID-19 vaccine. Vaccine. 2020;38:5424-9. Chan N, Ong K, Siau C, Lee K, Peh S, Yacob S, Chia Y, Seow V, Ooi P. The lived experiences of a COVID-19 immunization programme: vaccine hesitancy and vaccine refusal. BMC Public Health. 2022;22:1-13. Wong L, Alias H, Wong P, Lee H, Abubakar S. The use of the health belief model to assess predictors of intent to receive the COVID-19 vaccine and willingness to pay. Human Vaccines & Immunotherapeutics. 2020;16:2204-14. Al-Mohaithef M, Padhi B. Determinants of COVID-19 Vaccine Acceptance in Saudi Arabia: A Web-Based National Survey . Journal of Multidisciplinary Healthcare. 2020;Volume 13:1657-63. Wang J, Jing R, Lai X, Zhang H, Lyu Y, Knoll M, Fang H. Acceptance of COVID-19 Vaccination during the COVID-19 Pandemic in China. Vaccines. 2020;8:482. Wong L, Wong P, Abubakar S. Vaccine hesitancy and the resurgence of vaccine preventable diseases: the way forward for Malaysia, a Southeast Asian country. Human Vaccines & Immunotherapeutics. 2020;16:1511-20. Ali S, Ahmad F, Noor M. COVID-19 Vaccine Hesitancy in Kedah, Malaysia: A Qualitative Study. Int Res J Pharm Med Sci. 2022;5:46-50. Saunders B, Sim J, Kingstone T, Baker S, Waterfield J, Bartlam B, Burroughs H, Jinks C. Saturation in qualitative research: exploring its conceptualization and operationalization. Quality & Quantity. 2018;52:1893-907. Creswell J, Hirose M. Mixed methods and survey research in family medicine and community health. Family Medicine and Community Health. 2019;7:e000086. Korstjens I, Moser A. Series: Practical guidance to qualitative research. Part 4: Trustworthiness and publishing. European Journal of General Practice. 2018;24:120-4. Vaz O, Ellingson M, Weiss P, Jenness S, Bardají A, Bednarczyk R, Omer S. Mandatory Vaccination in Europe. Pediatrics. 2020 Feb;145:e20190620. Harapan H, Wagner A, Yufika A, Winardi W, Anwar S, Gan A, Setiawan A, Rajamoorthy Y, Sofyan H, Mudatsir M. Acceptance of a COVID-19 Vaccine in Southeast Asia: A Cross-Sectional Study in Indonesia. Frontiers in Public Health. 2020;8. Kaplan A, Sahin M, Parildar H, Adadan Guvenc I. The willingness to accept the COVID‐19 vaccine and affecting factors among healthcare professionals: A cross‐sectional study in Turkey. International Journal of Clinical Practice. 2021;75:e14226. Ministry of Health Malaysia. COVID-19 Statistical Report. 2020. Accessed on 15 September 2021. Lim K, Chan Y, Noor Ani A, Rohani J, Siti Norfadhilah Z, Santhi M. Complete immunization coverage and its determinants among children in Malaysia: findings from the National Health and Morbidity Survey (NHMS) 2016. Public Health. 2017;153:52-7. Recommendation of Who Strategic Advisory Group of Experts (Sage) on Immunization. Pediatric Clinical Practice Guidelines & Policies. 2015. on 30th October 2021;:1102-. Awadh A, Hassali M, Al-Lela O, Bux S, Elkalmi R, Hadi H. Immunization knowledge and practice among Malaysian parents: a questionnaire development and pilot-testing. BMC Public Health. 2014;14:1-7. Bell S, Clarke R, Mounier-Jack S, Paterson P. Parents’ and guardians’ views on the acceptability of a future COVID-19 vaccine for themselves and their children: cross-sectional survey and qualitative interview data.. London School of Hygiene & Tropical Medicine,. 2020;. García L, Cerda A. Contingent assessment of the COVID-19 vaccine. Vaccine. 2020;38:5424-9. Ghazali W, Mohamed S, Nasir N, Yusoh M. The Coverage Of Vaccination In The Malay Newspapers: An Exploratory Study. Asian Journal of Applied Communication e-ISSN. 2020;2682:7506. Wong L, Wong P, Abubakar S. Vaccine hesitancy and the resurgence of vaccine preventable diseases: the way forward for Malaysia, a Southeast Asian country. Human Vaccines & Immunotherapeutics. 2020;16:1511-20. Bell S, Clarke R, Mounier-Jack S, Walker J, Paterson P. Parents’ and guardians’ views on the acceptability of a future COVID-19 vaccine: A multi-methods study in England. Vaccine. 2020;38:7789-98. Ministry of Health Malaysia. COVID-19 Latest Update. 2020;. Altmann S, Milsom L, Zillessen H, Blasone R, Gerdon F, Bach R, Kreuter F, Nosenzo D, Toussaert S, Abeler J. Acceptability of App-Based Contact Tracing for COVID-19: Cross-Country Survey Study. JMIR mHealth and uHealth. 2020;8:e19857. Cho H, Ippolito D, Yu Y. Contact tracing mobile apps for COVID-19: Privacy considerations and related trade-offs.. Kapoor H, Kaufman J. Meaning-Making Through Creativity During COVID-19. Frontiers in Psychology. 2020;11. Rumetta J, Abdul-Hadi H, Lee Y. A qualitative study on parents’ reasons and recommendations for childhood vaccination refusal in Malaysia. Journal of Infection and Public Health. 2020;13:199-203. Hwang J, Cho H, Im H Bin, Jung Y, Choi S. Malaysian Journal of Medicine and Health Sciences. Malaysian Journal of Medicine and Health Sciences. 9346;:2636. Deml M, Notter J, Kliem P, Buhl A, Huber B, Pfeiffer C, Burton-Jeangros C, Tarr P. “We treat humans, not herds!”: A qualitative study of complementary and alternative medicine (CAM) providers’ individualized approaches to vaccination in Switzerland. Social Science & Medicine. 2019;240:112556.